TRAINING FOR THE PREPARATION OF SCIENTIFIC ARTICLES FOR LECTURERS AND STUDENTS AT HIGHER EDUCATION IN BANTEN - Sri Mulyono; Sumarsid Sumarsid; Muhsin Muhsin; Ratih Kusumastuti; Wahyu Wiguna; Ahmad Mukhlis (International Journal of Engagement and Empowerment, 2023)
Scientific article writing training is very important in improving the skills of students and lecturers in compiling good and correct scientific articles. With this training, it is hoped that students and lecturers can acquire the knowledge and skills needed to face challenges in the academic world, and can gain recognition for the scientific work they produce through publication in accredited national journals and reputable international journals. The purpose of this training is to increase the understanding of students and lecturers in writing good and correct scientific articles and it is hoped that participants will gain knowledge and skills in compiling scientific articles in accordance with standards set by accredited national journals and reputable international journals. The method used in scientific article writing training through zoom meetings with a combination of lecture and practice methods is a very appropriate method. With this method, participants can follow the training material more easily and can immediately practice writing good and correct scientific articles. The participants who took part in the training were approximately 100 people, a large enough number of participants for a scientific article writing training. The results of the service activities carried out were very satisfying, with increased partner knowledge in terms of writing scientific articles. This training can also help students to realize the importance of scientific publications in the context of disseminating knowledge. With scientific publications, students and lecturers can make a real contribution to the academic world and can help improve the quality of education in Indonesia